Bioavailability of Glucosinolates and Their Breakdown Products: Impact of Processing - Barba, Francisco J.; Nikmaram, Nooshin; Roohinejad, Shahin; Khelfa, Anissa; Zhu, Zhenzhou; Koubaa, Mohamed (Frontiers in Nutrition, 2016)
Glucosinolates are a large group of plant secondary metabolites with nutritional effects, and are mainly found in cruciferous plants. After ingestion, glucosinolates could be partially absorbed in their intact form through the gastrointestinal mucosa. However, the largest fraction is metabolized in the gut lumen. When cruciferous are consumed without processing, myrosinase enzyme present in these plants, hydrolyzes the glucosinolates in the proximal part of the gastrointestinal tract to various metabolites such as isothiocyanates, nitriles, oxazolidine-2-thiones and indole-3-carbinols. When cruciferous are cooked before consumption, myrosinase is inactivated and glucosinolates transit to the colon where they are hydrolyzed by the intestinal microbiota. Numerous factors such as storage time, temperature, and atmosphere packaging, along with inactivation processes of myrosinase are influencing the bioavailability of glucosinolates and their breakdown products. This review paper summarizes the assimilation, absorption, and elimination of these molecules, as well as the impact of processing on their bioavailability.